Support Mechanisms and Vulnerabilities in Relation to PTSD in Veterans of the Gulf War, Iraq War, and Afghanistan Deployments: A Systematic Review. Issue 3 (13th May 2013) - Wright, Breanna K.; Kelsall, Helen L.; Sim, Malcolm R.; Clarke, David M.; Creamer, Mark C.
<x xml:space="preserve">Abstract</x> Pretrauma factors of psychiatric history and neuroticism have been important in highlighting vulnerability to posttraumatic stress disorder (PTSD), whereas posttrauma support mechanisms have been associated with positive health and well‐being outcomes, particularly in veterans. The relationship between these factors and PTSD has not been the subject of a systematic review in veterans. An online search was conducted, supplemented by reference list and author searches. Two investigators systematically and independently examined eligible studies. From an initial search result of 2, 864, 17 met inclusion criteria. A meta‐analysis of unit cohesion involving 6 studies found that low unit cohesion was associated with PTSD, standardised mean difference of −1.62, 95% confidence interval (CI) [−2.80, −0.45]. A meta‐analysis of social support involving 7 studies found that low social support was associated with PTSD, standardised mean difference of − 12.40, 95% CI [−3.42, −1.38]. Three of 5 studies found a significant relationship between low‐family support and PTSD; insufficient data precluded a meta‐analysis. Regarding pretrauma vulnerability, 2 studies on psychiatric history and 1 on neuroticism found positive relationships with PTSD. Posttrauma factors of low support were associated with higher reporting of PTSD. Cross‐sectional methodology may be inadequate to capture complex relationships between support and PTSD; more longitudinal research is required.